Basics of planning a pre-competitive mesocycle during taekwondo training - Koshcheyev, A.; Dolbysheva, N. (Journal of Physical Education and Sport, 2021)
The purpose. To reveal and determine the effectiveness of planning a precompetitive mesocycle according to the «pendulum» principle in the training system of taekwondo athletes based on the definition of training and competitive loads, rational construction and duration of microcycles. The object. The training process of taekwondo fighters in the pre-competition mesocycle. Participants. The research was carried out during the Championships and Cups of Ukraine, in which 114 athletes in taekwondo of the junior age category (age 15-17 years) took part, on which the time and heart rate indicators were recorded when analyzing 248 performances (fights). Two groups were formed: the control group and the core group. Each group consisted of 10 athletes, aged 15-17 year. Results. The analysis of heart rate indicators in the process of competitive activity allowed us to develop a ranking of heart rate in points from 1 to 10, as well as a scale of intensity of training and competitive loads from 1 to 33. The information content of the developed scales is very high, since a high degree of connection between the intensity of training loads and the heart has been revealed rate and technical actions (r = 0.78 at p> 0.001; r = 0.71 at p> 0.001; r = 0.73 at p> 0.01). It was found that the construction of a precompetitive mesocycle according to the «pendulum» principle in the training system of taekwondo athletes at the stage of maximum realization of individual capabilities is effective, which is confirmed by the results obtained at the end of this mesocycle. There was revealed a significant increase in physical fitness indicators and coefficients of competitive activity (p=0.05). The stabilization of the mental state (from 0 to 3 points) and the accuracy of muscle efforts (from -08 kg to 1.0 kg) were determined. Conclusions. Planning a precompetitive mesocycle according to the «pendulum» principle in the taekwondo training system allows planning significant training loads in waves with an emphasis on the recovery of the athlete's body in the range from 1 to 10 points, which made it possible to increase the level of physical fitness, the coefficients of competitive activity, stabilize the mental state, the accuracy of muscular efforts and sports performance. Keywords:taekwondo, taekwondo fighters, heart rate, planning, pre-competition mesocycle, the «pendulum» principle, the stage of maximum realization of individual capabilities, training load, training load intensity.